1990
DOI: 10.1007/bf00052605
|View full text |Cite
|
Sign up to set email alerts
|

Studies of human breast cancer metastasis using nude mice

Abstract: Athymic nude mice have been used in recent years to study the biology of human tumors and to assess therapeutic responses in vivo rather than just in vitro. Some human tumors metastasize in nude mice, providing model systems for analyzing various aspects of the metastatic phenotype of human neoplasms. For breast carcinomas, however, the tumor-take rate of surgical specimens is low, and only a limited number of cell lines proliferate in nude mice. The site of injection of the breast carcinoma cells is important… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
52
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(54 citation statements)
references
References 57 publications
2
52
0
Order By: Relevance
“…B, nonparametric ANOVA analysis of HBP1 mRNA expression. HBP1 levels for normal (25)(26)(27)(28)(29)(30)(31)(32)(33) in top ), all invasive (1-23), invasive-low HBP1 (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15), and invasive-high HBP1 (17-23) were compared by nonparametric ANOVA. Dunn's multiple comparisons test was then used.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…B, nonparametric ANOVA analysis of HBP1 mRNA expression. HBP1 levels for normal (25)(26)(27)(28)(29)(30)(31)(32)(33) in top ), all invasive (1-23), invasive-low HBP1 (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15), and invasive-high HBP1 (17-23) were compared by nonparametric ANOVA. Dunn's multiple comparisons test was then used.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, we assessed the consequences of an HBP1 knockdown on invasiveness and proliferation of MDA-MB-231 cells. These cells remain an established model for invasion and for tumorigenic proliferation studies, including anchorage-independent growth and tumor formation in orthotopic xenograft models (30,31). As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…An associated correlate to this ideal is that the model used should also mimic the human disease state or condition. The MDA435/ LCC6 ascites tumor model is a direct derivative of the estrogen receptor negative, invasive and metastatic MDA-MB-435 cell line [34][35] and has been characterized as such by isotype and karyotype analysis. 20 It has been suggested that the coexpression of molecular markers in neoplastic transformation functions as a significant prognostic correlate for recurrence, and that the number of coexpressed markers is directly related to this significance.…”
Section: Discussionmentioning
confidence: 99%
“…At present, numerous breast carcinoma cell lines established from primary solid human breast carcinoma or from the metastatic pleural fluids are available for various research (Nordquist et al, 1975;Engel and Young, 1978;Langlois et al, 1979;Whitehead et al, 1983;Chu et al, 1985;Mehta et al, 1992;1995b;Watanabe et al, 1992;Slooten et al, 1995); however, only a limited number of these cell lines are tumorigenic in mice, and only two to three of these cell lines show distant metastasis when transplanted s.c. into athymic mice (Shafie and Liotta, 1980;Price et al, 1990;Brunner et al, 1992;Mehta et al, 1993). In addition the incidence of metastasis in these cell lines varies in different laboratories (Shafie and Liotta, 1980).…”
Section: Discussionmentioning
confidence: 99%
“…In most cases, xenografts originated in vivo in experimental animals preserve many of the original phenotypic, biological and genotypic characteristics from which they originate (Giovanella et al, 1989;Mehta et al, 1995a). However, human breast carcinomas are difficult to grow in vitro in culture (Nordquist et al, 1975;Engel and Young, 1978;Langlois et al, 1979;Whitehead et al, 1983;Chu et al, 1985;Mehta et al, 1992; 1995b ;Watanabe et al, 1992) or in vivo in experimental animals (Sabestany et al, 1979;Shafie and Liotta, 1980;Rae-Venter and Reid, 1980;Giovanella et al, 1985;Price and Zhang, 1990;Hurst J, et al, 1993;Mehta et al, 1993), and they rarely metastasize when transplanted subcutaneously (Shafie and Liotta, 1980;Price et al, 1990;Brunner et al, 1992;Mehta et al, 1993).…”
mentioning
confidence: 99%